#TITLE_ALTERNATIVE# - HAMDI ARZI (NIM : 10208057); Pembimbing : Dr. Rizal Kurniadi, S.Si.,M.Si., YUDHA
Boiling is the phenomena when a fluid changes phase from liquid to vapor bubbles. It often we see in everyday life, especially when cooking. Benefits of boiling water also varied ranging for cooking, cooling the reactor, to power plants. Obviously this is a very interesting phenomena to watch. Modeling done by solving the Navier-Stokes and heat transfer in an existing domain mesh. By dividing the continuous area as small sections, the calculation will be done more easily. By using simulations, we will get results more easily observed than just the equation. The hardware used is a laptop with i7 processor, while the COMSOL software is MULTIPHYSIC. The purpose of modeling is to understand and master how to use the software, and also to understand the physical aspects involved in such modeling. Because if you do not understand his physical aspect we will not be able to develop better models. Modeling is done by first trying to make my own existing model, then see if the results are in line with the reference or not. Then progressed to more models of real (complex) with the addition of several variables and changes in boundary conditions. Last is the addition of a continuous flow on an existing model and modify the model so that it looks real. Thu changes will be observed from this modeling is the volume fraction. Volume fraction is the ratio of the observed fluid phase. From here we will conclude the effect of changing variables and also the addition of a continuous flow on a model that we make.